Protective effects of Syzygium aromaticum oil (Clove) against acrylamide induced hepatic, renal, and testicular toxicity in rats - Elkomy, Ashraf; Aboubakr, Mohamed; Ibrahim, Samar; Abdelhamid, Yasmine (International Journal of Pharmacology and Toxicology, 2018)
This study aimed to investigate the possible protective role of clove oil against acrylamide induced oxidative damage and impairment of liver, kidney, and testicular functions in albino rats. The apparent oxidative damage was associated with evident hepatic, renal, and testicular dysfunction, which was confirmed in histopathological lesions, and increased serum aspartate aminotransferase and alanine aminotransferase activities. Acrylamide decreased serum total protein and albumin contents; increased urea and creatinine contents. Acrylamide also reduced testosterone concentration. Treatment of acrylamide intoxicated rats with clove oil minimized liver, kidney, and testicular histopathological changes and normalized their functions. Our findings demonstrate that acrylamide is not only associated with hepatotoxicity but also nephrotoxicity and testicular toxicity. Clove oil administration provided substantial organ protection against hepatic, renal, and testicular dysfunction induced by acrylamide, which was possibly mediated through their antioxidant activities.Â Â Â